Association between gender and self-assessment skills amongst Japanese dental students - Lang Liang; Masako Nagasawa; Vivian Ha; Amy J. Lin; Yosuke Akiba; Nami Akiba; Shelyn A. Yamakami; Katsumi Uoshima; Hiroe Ohyama (Elsevier, 2024)
Background/purpose: Self-assessment in dental education is considered a fundamental skill for proficient oral healthcare providers. While previous studies looked at self-assessment in education, few have done so at Japanese institutions. This study aimed to assess potential associations between gender and self-assessment skills in Japanese dental students. Materials and methods: Dental students from Niigata University (n = 301) completed preclinical prosthodontic exercises and self-assessed their practical exam performance. Three calibrated faculty evaluated students' work using the same rubric. The difference between student self-assessment score and mean faculty grade was defined as the student-faculty (S-F) gap, indicating how accurately students evaluated their work. The gap scores were stratified by quartiles by faculty grade and by gender. Regression analysis was used to investigate potential associations. Results: Students mean S-F gap was 2.9 ± 10.5 % with a significant negative association to faculty grades (coefficient, −0.32; P < 0.001). There was no significant difference between male and female students for faculty grades, self-assessment scores, and S-F gaps. When stratified by quartile, mean S-F gaps of bottom quartile students (5.7 ± 11.9 %) were significantly higher than the rest of the class (1.9 ± 9.8 %; P = 0.01), while the mean S-F gaps of students in the top quartile (−0.8 ± 10.2 %) were significantly lower than the rest of the class (4.2 ± 10.3 %; P < 0.001). Conclusion: Niigata University students generally overestimated their performance. Students with higher faculty grades self-assessed themselves more accurately than students with lower faculty grades. Gender did not influence S-F gaps, despite dentistry in Japan shifting toward a female-dominated field.